Comparative Efficacy of Single-Dose versus Multiple-Dose Antibiotic Prophylaxis in Reducing Postoperative Infections in Elective Cesarean Deliveries: Antibiotic Prophylaxis in Cesarean Deliveries - Arifa, .; Zubair, Roma; Gul, Saima; Sheraz, Misbah; Rani, Nadia; Safdar, Sundas; Ullah, Naqeeb (Pakistan Journal of Health Sciences, 2024)
Cesarean Sections (CS) were common surgeries that may lead to complications like endometritis and Surgical Site Infections (SSIs). While prophylactic antibiotics reduce these risks, the ideal dosing regimen remains debated. Objective: To evaluates whether a single or multiple-dose antibiotic regimen offers better protection against infections in patients undergoing planned cesarean sections. Methods: A six-month quasi-experimental study was conducted from October 1, 2020, to March 30, 2021, at Lady Reading Hospital in Peshawar. Eighty-two women scheduled for elective CS were assigned into two groups: one received a single 1g dose of intravenous cefazolin before surgery, and the other received the same initial dose followed by two additional doses every eight hours. Primary outcomes assessed were the incidence of endometritis and SSIs within 30 days post-surgery. Results: Postpartum infections were significantly lower in the multiple-dose group (4.9%) compared to the single-dose group (19.5%, p = 0.039). The multiple-dose group also had fewer SSIs (4.9% vs. 14.6%, p = 0.140) and no cases of endometritis (0% vs. 4.9%, p = 0.154), though these differences were not statistically significant. There were no significant differences in adverse drug reactions, hospital stay duration, or antibiotic resistance development between the groups. Conclusions: Multiple-dose antibiotic regimens may reduce infection rates in planned CS without increasing adverse effects or antibiotic resistance. Further studies were needed to confirm these findings and optimize prophylactic strategies.